Noise induced re-entrant transitions in exciton bistable system - Gudyma, Yu.; Ivans'kii, B.; Semenko, O. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2006)
We study a re-entrant transition in an exciton bistable system under the influence of multiplicative noise. The re-entrant behavior is predictable for specific values of the system control parameter when increasing the multiplicative noise intensity. The system of Wannier-Mott excitons exhibits bistable ↔ monostable transitions in a window of intermediate amplitudes of the multiplicative noise intensity demonstrating its destructive and constructive role.